A numerical study on bio-inspired aerofoils oscillating in tandem - Chua, Kok Nam (2018)
Previous study by Flint et al. [1] investigated the flow behaviour of a single bio-inspired corrugated aerofoil in oscillatory pitching motion. In that paper, the effects of varying frequencies and amplitudes of oscillation were investigated. As a dragonfly has two pairs of wings, a natural progression would be to expand on these findings into investigating the effects and flow interactions between two tandemly-positioned aerofoils in synchronised pitching motion. This study aims to establish a better understanding of the inter-wings flow interactions, and how changes in the oscillation frequencies and amplitudes could affect the lifting and thrust performance of both the fore- and aft-aerofoils. Two-dimensional flow simulation at Re=14,000 was carried out on five different cases of motion, by first varying the oscillation frequency, then the oscillation amplitude. It was observed that through the aft-aerofoil’s interaction with fore-aerofoil’s wake, the aft-aerofoil consistently showed an increase in the resultant maximum lift in both the positive and negative directions. The amount of augmentation however was found to be unsymmetrical, with a larger amount of improvement observed towards the negative lifting direction. As a result, when considering the aft-aerofoil’s mean lifting performance through one full oscillation, it was found to have performed worse than the fore-aerofoil. The thrust performance for the aft-aerofoil was found to largely depend on the specific vortex dynamics of each motion case, and no obvious trend was observed as frequency and amplitude was varied. It was also observed that positive thrust was only produced at cases with large rates of aerofoil rotation, where St>0.4, consistent with the findings of the single-aerofoil study. At zero phase difference, the resultant vortex dynamics had significant influence over the lifting performance of the aft-aerofoil, but with little influence over its thrust performance.